La no responsabilidad de los agentes de retención vulnera la suficiencia recaudatoria del estado. - Chuquizan Irua, Anabela (2025)
The tax system in Ecuador is one of the fundamental pillars for guaranteeing a sufficient tax collection, and with this action be able to finance the economic and social development of this country. In this research, it has been observed that the Organic Law for the Economic Development and Fiscal Sustainability (LODESF) establishes a Simplified Regime for Entrepreneurs and Popular Business (RIMPE) to facilitate tax inclusion of small business contributors. However, the exclusion of these passive agents as withholding agents for VAT and Income taxes has generated serious concerns about the impact on tax collection. For this reason, the objective of this research is to analyze how the exclusion of passive agents of the RIMPE regime as agents of tax collection directly affects tax collection, so to promote a reform of article 97.7 paragraph 2 of the LODESF. The methodology used was quantitative with a descriptive and explanatory approach, based on surveys carried out to 24 people related professionally in the tax accounting area. Results highlight that there is an urgent need to reform the tax legislation to strengthen the tax collection capacity of the State and thus guarantee that all economic sectors, including the small entrepreneurs, contribute adequately to the financing of the public policies.